Spanish PIBID: a space that brings school and future teachers together (2021)
This paper proposes a reflection on the Spanish Teaching Initiation Institutional Scholarship Program [Spanish PIBID] at the Federal University of Santa Catarina as a space that brings together schools and future teachers, in schools of the Florianópolis Metropolitan Region, showing actions and challenges faced for the consolidation of the program in the region. Based on a research done with the participants of the Spanish subproject—2012-2020—the project was analyzed from the perspective of PIBID teacher trainees, according to the topics highlighted by them, such as the relation between theory and practice, their presence in school, or the relation between the university and basic school. Based on official data on filled and unfilled school capacity, current challenges faced by teaching programs in universities were also taken into account, especially in the case of Spanish as a foreign language program, considering the need to keep teaching-fostering public policies in place. As a formative experience, the subproject is perceived as rewarding, having as a theoretical basis the training of reflective teachers and researchers, concerned with collaborating to maintaining high quality standards for public school as an institution that educates critical and autonomous citizens.